2010
DOI: 10.1088/0741-3335/52/5/055009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrostatic and electromagnetic synchronization of drift waves and suppression of drift wave turbulence in a linear device

Abstract: Abstract. Experiments in a cylindrical magnetized plasma on the control of drift waves by means of two different spatiotemporal open-loop control systems -an electrostatic and an electromagnetic exciter -are reported. The drift wave dynamics is controlled by a mode-selective signal created with azimuthal arrangements of eight electrodes and eight saddle coils, respectively. Nonlinear interaction between the control signals and drift waves is observed, leading to synchronization of coherent drift waves and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The guided behavior is reminiscent of resonance cones predicted for low-frequency electrostatic waves [51][52][53][54][55] , as well as shear Alfvén waves 34 , but these scenarios are not consistent with the high collisionality (τ −1 ei /ω ≈ 20 ≫ 1) of the edge, nor the driven resonance around the QCM. Experiments in linear devices have shown that exciting mode-selective parallel currents is the essential ingredient for coupling to drift waves, and that this may be done inductively 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guided behavior is reminiscent of resonance cones predicted for low-frequency electrostatic waves [51][52][53][54][55] , as well as shear Alfvén waves 34 , but these scenarios are not consistent with the high collisionality (τ −1 ei /ω ≈ 20 ≫ 1) of the edge, nor the driven resonance around the QCM. Experiments in linear devices have shown that exciting mode-selective parallel currents is the essential ingredient for coupling to drift waves, and that this may be done inductively 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in experiments examining nonlinear interaction between a driven mode and a coherent drift wave structure on a linear device, Brandt et al 33 observed frequency pulling and the appearance of sidebands in the fluctuation spectra. These features are not apparent in the fluctuation spectra obtained during Shoelace antenna operation, though higher antenna power may be needed to access this behavior.…”
Section: Transfer Function Analysismentioning
confidence: 99%
“…Drift-wave turbulence is generally believed to be responsible for the anomalous crossfield particle transport [23], and its control and suppression therefore is of great importance to the performance of magnetic confinement fusion devices, e.g., the tokamaks [24]. Over * Corresponding author: wangxg@snnu.edu.cn the past two decades, there have been continuous attempts in extending the techniques developed in chaos control to the suppression of drift-wave turbulence, in which a variety of theories and techniques have been proposed [25][26][27][28][29][30][31][32]. In the regime of weak turbulence, by use of the technique of timedelay autosynchronization (TDAS) [33], it has been shown by a series of studies that the chaotic temporal behavior of the drift waves in cylindrical magnetized plasmas can be tamed to be periodic [25,27,31].…”
Section: Introductionmentioning
confidence: 99%
“…In the regime of weak turbulence, by use of the technique of timedelay autosynchronization (TDAS) [33], it has been shown by a series of studies that the chaotic temporal behavior of the drift waves in cylindrical magnetized plasmas can be tamed to be periodic [25,27,31]. Moreover, by the strategy of open-loop synchronization, namely the mode-selective control, it has been shown recently that the complicated spatial behavior of the weakly developed drift-wave turbulence can be also successfully controlled (synchronized) to a predefined pattern of regular spatial structure [29,30]. More recently, by use of the method of pinning coupling, it has been shown that both the spatial and temporal behaviors of the drift-wave turbulence can be efficiently regulated into different spatiotemporal patterns, given the pinning strength is larger to some critical value [34].…”
Section: Introductionmentioning
confidence: 99%
“…In that way it is possible to have a very accurate description of the space time behavior of the plasma [10,11,7]. In addition it is worth noticing that it is also possible to act on the plasma using electrodes directly in contact with the plasma, producing for example a mode locking between the injected sinusoidal signal and the plasma dynamics [12,13]. Moreover, in the SOL region of tokamaks where the field lines are connected to the wall, a parallel current created by probes acts on perpendicular dynamics [14].…”
Section: Introductionmentioning
confidence: 99%